Electron beam irradiation for the formation of thick Ag film on Ag3PO4. Issue 37 (8th June 2020) - Paulo de Campos da Costa, João; Assis, Marcelo; Teodoro, Vinícius; Rodrigues, Andre; Cristina de Foggi, Camila; San-Miguel, Miguel Angel; Pereira do Carmo, João Paulo; Andrés, Juan; Longo, Elson
Abstract : This study demonstrates that the electron beam irradiation of materials, typically used in characterization measurements, could be employed for advanced fabrication, modification, and functionalization of composites. Abstract : This study demonstrates that the electron beam irradiation of materials, typically used in characterization measurements, could be employed for advanced fabrication, modification, and functionalization of composites. We developed irradiation equipment using an electron beam irradiation source to be applied in materials modification. Using this equipment, the formation of a thick Ag film on the Ag3 PO4 semiconductor is carried out by electron beam irradiation for the first time. This is confirmed by various experimental techniques (X-ray diffraction, field-emission scanning electron microscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy) and ab initio molecular dynamics simulations. Our calculations demonstrate that, at the earlier stages, metallic Ag growth is initiated preferentially at the (110) surface, with the reduction of surface Ag cations forming metallic Ag clusters. As the (100) and (111) surfaces have smaller numbers of exposed Ag cations, the reductions on these surfaces are slower and are accompanied by the formation of O2 molecules.